Cost-Effectiveness Analyses of Home Parenteral Nutrition for Incurable Gastrointestinal Cancer Patients - Li, Wenqian; Guo, Hanfei; Li, Lingyu; Cui, Jiuwei (Frontiers in Oncology, 2022)
Background: Appropriate nutritional support including supplemental home parenteral nutrition (sHPN) could bring prognosis benefit and improve the quality of life (Qol) for malnourished cancer patients. We aimed to explore the cost-effectiveness of sHPN for incurable gastrointestinal cancer patients from the Chinese healthcare perspective. Method: Clinical data was extracted from a randomized controlled trial (NCT02066363). Patients were randomized into sHPN group or non-sHPN group (receiving best practice nutritional care). A Markov model was established with a 6-week cycle length. Costs were acquired from local hospitals, effect parameters included quality-adjusted life year (QALY), Qol, body mass index, fat free mass (FFM), FFM index, handgrip strength and six minutes walking test. Sensitivity analyses were conducted with a willingness-to-pay (WTP) set at 3 per capita gross domestic product ($29307/QALY). Results: When considering QALY as utility, the incremental cost-effectiveness ratio (ICER) was $24289.17 with an incremental cost of $2051.18 and an incremental QALY of 0.0844 between sHPN group and non-sHPN group. Further, we explored the cost-effectiveness of sHPN from multi-dimensions, where we analyzed various effect parameters at different visits, results showed a superior benefit of patients in sHPN group except for handgrip parameter at visit 2. Sensitivity analysis demonstrated the influence of utilities in sHPN group, sHPN group was still cost-effective with a WTP of $2500/QALY. Conclusion: sHPN was cost-effective for patients with incurable gastrointestinal cancer in China, which suggested further applications in clinical practice and provided references for clinical decision and pricing.